Chironomidae larvae associated with Eichhornia azurea leaf detritus: decomposition community structure and colonization dynamics - da Silva, Carolina Vieira [UNESP] (2018)
Chironomidae stand out among aquatic insects associated with organic matter decomposition due to their abundance, cosmopolitan distribution, the varied forms in which they use detritus, as well as the feeding plasticity of their larvae. The objective of this study was to investigate the structure and composition of the Chironomidae community (Diptera) in the decomposition of Eichhornia azurea leaves in a marginal lake. The working hypothesis is that the taxonomic and functional density and richness of Chironomidae increase over time during the degradation of E. azurea leaves. Decomposition was analyzed in leaves kept in 2-mm mesh litter bags and collected at set successive sampling intervals. Significant differences were found in Chironomidae density and composition in the time scale. The density of individuals increased significantly during the experiment, in contrast to the taxonomic and functional richness. Subfamily Chironominae was the most representative in terms of density and taxonomic richness. The densities of taxa Labrundinia sp., Tanytarsus sp., Dicrotendipes sp., Endotribelos sp. Chironomus sp. and Ablabesmyia sp. were mainly responsible for intragroup similarity in the groups formed at each sampling time. In contrast, the taxonomic composition varied throughout the experiment with characteristic ecologic succession and dynamic stabilization of the colonizing community towards the end of the experiment. In conclusion, the Chironomidae community structure presented an increase in larva density during the experimental period associated with changes in taxon composition; however, the total taxonomic richness variation was low and functional richness did not vary.